2014
DOI: 10.3109/10826084.2014.880721
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Framing and Fear on Ratings and Impact of Antimarijuana PSAs

Abstract: A laboratory experiment, funded by the U.S. National Institutes of Health, involved 243 U.S. undergraduate students and employed a 2 (gain-framed vs. loss-framed) × 2 (high vs. low threat) plus control group pretest-posttest experimental design to assess the combined effects of frame (gain vs. loss) and level of threat of public service announcements (PSAs) about marijuana on attitudes, beliefs, and intentions related to marijuana, as well as the relationship of message condition to ratings of PSAs. Results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…A study focusing on sun protection showed that the relative effect of message framing is better understood in the context of perceived risk level and perceived effectiveness of the protection (Hwang, Cho, Sands & Jeong, 2012). Similar results were reported from a study looking at the complexity of the way frame and threat may interact (Zimmerman, Cupp, Abadi, Donohew, Gray, Gordon & Grossl, 2014). Using public announcements on marijuana as intervention messages, this study confirmed that loss-frames were more effective with high perceived risk, but strong effects were also noted with low perceived risk.…”
Section: Message and Mediumsupporting
confidence: 77%
“…A study focusing on sun protection showed that the relative effect of message framing is better understood in the context of perceived risk level and perceived effectiveness of the protection (Hwang, Cho, Sands & Jeong, 2012). Similar results were reported from a study looking at the complexity of the way frame and threat may interact (Zimmerman, Cupp, Abadi, Donohew, Gray, Gordon & Grossl, 2014). Using public announcements on marijuana as intervention messages, this study confirmed that loss-frames were more effective with high perceived risk, but strong effects were also noted with low perceived risk.…”
Section: Message and Mediumsupporting
confidence: 77%
“…Beaudoin & Hong, 2012;Primack, Kraemer, Fine, & Dalton, 2009;Stryker, 2003) and the influence of anti-cannabis media campaigns (e.g. Alvaro et al, 2013;Kang, Cappella & Fishbein, 2009;Zimmerman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…T A B L E 1 (Continued) The literature in this area advocates the use of the following types of appeals: fear (Zimmerman et al, 2014); humour (Iles & Nan, 2017); nurturance (Bleakley et al, 2015); risk type (Jones & Leary, 1994); sidedness (Lienemann & Siegel, 2018); framing (Zimmerman et al, 2014); social and self-esteem (Kim et al, 2018).…”
Section: Healthmentioning
confidence: 99%
“…Using content analysis, Niederdeppe et al (2017) found that anti-alcohol PSAs were consistent with the tenets of the EPPM, and to some extent, the ELM. In the area of anti-marijuana PSAS (Zimmerman et al, 2014) used the EPPM and prospect theory to find that avoiding loss-framed moderate threat messages is better and policy makers may use loss-framed low threat or gain-framed high/low threat appeals.…”
Section: Use Of Common Theoriesmentioning
confidence: 99%
See 1 more Smart Citation